A importância da análise ergonômica do trabalho na contestação da doença ocupacional - estudo de case em um indústria de panificação - Caldeira, Jaqueline de Queiroz (Universidade Federal de São Carlos, 2021)
Ergonomic Work Analysis (EWA) has been a great ally for understanding the work environment, making it possible to assess the factors that influence the performance and health of employees. In this analysis, several factors, stages and tasks developed by employees are evaluated, so that it is possible to determine which areas need improvements and require action to be taken to achieve the ergonomic requirements of workers, respecting their limits and needs. One of the tools used in an EWA, is the Suzanne Rodgers method, which is the same used in the ergonomic report studied in this work. The ergonomic report, applied in a bakery, analyzed the frequent and sporadic tasks performed by a confectioner and confectionery assistant, where three criteria were evaluated: level of effort, time of effort and effort per minute in the six main muscle groups of the human body, thus making it possible to determine the risk of accidents at work and occupational diseases, to which such employees were exposed.
The importance of ergonomic work analysis on occupational sickness contestation - a case study applied to baking industry
Keywords: Análise ergonômica do trabalho; Doença ocupacional; Suzanne Rodgers; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::ERGONOMIA; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::PROCESSOS DE TRABALHO